Policy for Providing Assistance for Micro, Small and Medium Enterprises (MSMEs) in the Covid-19 Pandemic Era (Maslahah Review of Government Policies) - Imaro Sidqi; Zulfatun Inayah; Suci Indah Sari; Mhd. Rasidin; Doli Witro (Jurnal Hukum Ekonomi Islam, 2021)
This article aims to find and explain several government policies in dealing with Micro, Small and Medium Enterprises (MSMEs) in Indonesia with a review of the problems in the era of the Covid-19 pandemic. This research is a qualitative research approach, namely the statute approach, the case approach, and the philosophical approach. The results showed that the rules put forward by the government aimed to uphold people’s rights, especially in matters of the economy. Based on the review of the issue, this is justified, and indeed MSME assistance from the government is to revive the decline of MSMEs caused by the Covid-19 pandemic. Besides, this policy is also in line with Islamic law’s objectives, such as protecting religion, soul, descent, reason, and property. Keywords: MSMEs, Covid-19, Maslahah, The Purpose of Islamic Law Abstrak Artikel ini bertujuan untuk mencari dan menjelaskan tentang beberapa kebijakan pemerintah dalam penanggulangan Usaha Mikro Kecil dan Menengah (UMKM) di Indonesia dengan tinjauan maslahah di era pandemi Covid-19. Penelitian ini merupakan penelitian kualitatif dengan pendekatan yaitu statute approach, case approach, dan philosophical approach. Hasil penelitian menunjukkan bahwa aturan yang disodorkan oleh pemerintah bertujuan untuk menegakkan hak-hak rakyat khususnya dalam perihal ekonomi. Berdasarkan tinjauan maslahah hal tersebut dibenarkan dan memang bantuan UMKM yang berasal dari pemerintah untuk membangkitkan kembali keterpurukan UMKM yang diakibatkan oleh pandemi covid-19. Selain itu, kebijakan tersebut juga sepaham dengan tujuan-tujuan hukum Islam seperti perlindungan terhadap agama, jiwa, keturunan, akal, dan harta. Kata Kunci: UMKM, Covid-19, Maslahah, dan Tujuan Hukum Islam